Kinetics of thorium and particle cycling along the U.S. GEOTRACES North Atlantic Transect. (July 2017) - Lerner, Paul; Marchal, Olivier; Lam, Phoebe J.; Buesseler, Ken; Charette, Matthew
Abstract: The high particle reactivity of thorium has resulted in its widespread use in tracing processes impacting marine particles and their chemical constituents. The use of thorium isotopes as tracers of particle dynamics, however, largely relies on our understanding of how the element scavenges onto particles. Here, we estimate apparent rate constants of Th adsorption ( k 1 ), Th desorption ( k −1 ), bulk particle degradation ( β -1 ), and bulk particle sinking speed ( w ) along the water column at 11 open-ocean stations occupied during the GEOTRACES North Atlantic Section (GA03). First, we provide evidence that the budgets of Th isotopes and particles at these stations appear to be generally dominated by radioactive production and decay sorption reactions, particle degradation, and particle sinking. Rate parameters are then estimated by fitting a Th and particle cycling model to data of dissolved and particulate 228, 230, 234 Th, 228 Ra, particle concentrations, and 234, 238 U estimates based on salinity, using a nonlinear programming technique. We find that the adsorption rate constant ( k 1 ) generally decreases with depth across the section: broadly, the time scale 1 / k 1 averages 1.0 yr in the upper 1000 m and (1.4–1.5) yr below. A positive relationship between k 1 and particle concentration ( P ) is found, i.e., k 1 ∝ P b, where b ≥ 1, consistent with the notion that k 1 increases with the number of surface sites available for adsorption. The rate constant ratio, K = k 1 / ( k − 1 + β − 1 ), which measures the collective influence of rate parameters on Th scavenging, averages 0.2 for most stations and most depths. We clarify the conditions under which K / P is equivalent to the distribution coefficient, K D, test that the conditions are met at the stations, and find that K / P decreases with P, in line with a particle concentration effect ( dK D / dP < 0 ). In contrast to the influence of colloids as envisioned by the Brownian pumping hypothesis, we provide evidence that the particle concentration effect arises from the joint effect of P on the rate constants for thorium attachment to, and detachment from, particles. Abstract : Highlights: A kinetic model of thorium and particle cycling is fit to GEOTRACES North Atlantic radionuclide and particle data. Processes missing from the model appear to be small compared to those encapsulated by the model. We find evidence of a general positive relationship between k1 and particle concentration across the North Atlantic. Thorium sorption and particle degradation jointly contribute to a particle concentration effect across the North Atlantic.